Acidentes de trabalho por esforços excessivos ou movimentos inadequados nas Instituições Públicas de Saúde Portuguesas - Martins, Matilde (2014)
In health institutions there are several risks, many of them related to the activity developed. Inappropriate movements or excessive efforts are next to pinprick the most frequent cause of accidents at work in the health institutions. Objective: to analyze the occupational accidents notified by inappropriate movements or excessive efforts in public health institutions in Portugal in the years 2009 and 2010. A retrospective cross-sectional study, for the period of January 1, 2009 to December 31, 2010. The sample consisted of 2101employees of Portuguese public institutions who had accident by overexertion or improper movement and notified. The information was obtained after authorization by the director of the ACSS, using the anonymous records of the inquiry service of accidents at work by the Ministry of Health, and recorded in a database program developed in Excel by ACSS. The data were transported and analyzed on the computer program SPSS (Statistical Package for Social Sciences) 21.0 version for Windows, using the descriptive statistics for the description of the variables and the inferential statistics, Chi-square test and Kruskal-vallis, to determine the association between absences to work and the number of days lost through the remaining variables. There have been a total of 2101 accidents by overexertion or improper movement. The year of 2010 and hospitals registered the largest number of notifications 1163 (55.4%) and 2017 (96%), respectively. The highest prevalence was found in the professional group of Operational Assistants (Auxiliary Medical a Action) 1016 (48.4%), in females 1624 (77.3%), with lower schooling at ninth grade 941 (44.8%), with more than 10 years of service time 872 (41.5%), perform shift schedule 1456 (69.3%) and aged over 40 years 1059 (50.4%). The accidents occurred on average to 12.0 hours ± 5.2 hours, in the first three hours of the start of work 1062 (50.6%), in the first two days of work in relation to the last day of weekly rest 995 (45.0%) and inpatient services 939 (44.7%). The most frequent type of injury were sprains and muscle sprains 975 (46.7%) and the body part most affected by this type of accident was the trunk 1108 (52.7%). Caused absence to work 1322 (62.9%), totaling 49152 days on average missed 24 days per accident. Statistically significant association was found between absences to work and the professional group, the level of schooling, age and type of injury. The same association was verified for the average number of days lost. Conclusion: there was a high prevalence of accidents by overexertion or improper movement. Other studies are suggested to improve the knowledge on the occurrence of the accident, the reality of care, and the results of preventive and interventive actions.